Legibilidade dos relatórios de sustentabilidade: Análise da influência da governança corporativa e complexidade organizacional - Costa Filho, Francisco Carlos da (2023)
This research defends the thesis that corporate governance and organizational complexity influence the level of readability of sustainability reports. Given the relevance of the disclosure of sustainability reports, the general objective of this work is to investigate the influence of corporate governance and organizational complexity on the level of readability of sustainability reports. Using documentary procedures and archival data, with the application of statistical tools, Brazilian non-financial companies that publish sustainability reports in English between 2019 and 2022 are analyzed. As measures of Readability - the dependent variable - the Bog Index, Flesch-Kincaid Grade Level and Total Words models are used. As measures of Corporate Governance, the differentiated governance segment, the external assurance of the sustainability report and the number of members of the board of directors are used. For Organizational Complexity, the variables of company size, number of business segments, age and organizational life cycle were used. The results show that over the period analyzed more companies have made an effort to disclose their sustainability reports in English, however, more recent reports have worse readability indicators. In general, the reports are poorly readable and similar to each other, indicating a pattern of isomorphism in the writing and preparation of disclosures. The regression results show that only readability by total words is influenced by governance and complexity. It is believed that issues related to the process of translating reports and language characteristics present readability problems for English-language metrics. It is concluded that external assurance carried out by bigfour, larger boards of directors and more complex companies issue longer sustainability reports in different periods. The results contribute to a deeper understanding of the subject insofar as the assumptions of the Agency Theory are rejected and the precepts of the Contingency Theory are confirmed, revealing problems with the readability of sustainability reports issued by Brazilian companies.